Impact of an Antimicrobial Stewardship Program Led OPAT Program on Clinical Complications and Frequency of Hospital Readmissions. (4th October 2017) - Carr, J Andrew; Baddley, John W; Heath, Sonya; Lee, Rachael A; McCarty, Todd P
Abstract: Background: Treatment of serious bacterial infections with Outpatient Parenteral Antibiotic Therapy (OPAT) has provided patients (patients) the opportunity to complete treatment safely and effectively, while avoiding complications, and prolonged hospitalization. Despite the benefits, considerable risks with drug-related and central venous catheter (CVC)-related complications exist. We sought to improve clinical outcomes of our program by implementing intensive monitoring in partnership with our antimicrobial stewardship program (ASP) with a goal of decreasing the frequency of complications as well as hospital readmission rates and lengths of stay (LOS). Methods: A retrospective study was conducted including all patients discharged from the Birmingham VA Medical Center on OPAT from January 1, 2015 to December 31, 2016. The start date coincides with ASP development of a physician and pharmacist led OPAT program, working closely with home health agencies. Data collection included baseline demographics, antibiotic indication, antibiotic therapy received, and laboratory monitoring. Clinical outcomes included frequency and types of drug-related complications, CVC complications, hospital admission rate due to complications, and hospital days avoided. Results: In the study period, 299 patients were discharged on OPAT. They were 96.9% male, and the average age was 64 (Table 1). The average number of hospital days avoided was 32.1. The most common indication was osteomyelitis (Table 1). There were 82 complications in 78 (26%) patients, almost half were acute kidney injury, defined as a rise in serum creatinine requiring a change in antibiotic dosing (Table 2). These led to 25 hospitalizations (32% of patients with complications, 8.3% overall) with another 5 patients being hospitalized for unrelated reasons. Conclusion: Our medical center instituted an ASP led practice of closely monitoring and directing care with the local home health agencies due to concerns about patient safety. In doing so, we have realized a low rate of complications and an ability to manage the majority while remaining as an outpatient, with the exceptions of CVC-related complications and encephalopathy. Our data supports the center's efforts and choice to dedicate resources to improving this increasingly popular treatment. Disclosures: All authors: No reported disclosures.